2008
DOI: 10.1053/j.gastro.2008.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative Colitis Is a Disease of Accelerated Colon Aging: Evidence From Telomere Attrition and DNA Damage

Abstract: Background & Aims-Telomere shortening is implicated in cancer and aging, and might link these two biological events. We explored this hypothesis in ulcerative colitis, a chronic inflammatory disease that predisposes to colorectal cancer and where shorter telomeres have been associated with chromosomal instability and tumor progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
128
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(143 citation statements)
references
References 43 publications
13
128
1
1
Order By: Relevance
“…33,34 Especially in those with ulcerative colitis, hTERT overexpression has been associated with induction of CIN, 34 possibly an effect of oxidative damage secondary to inflammation. 35 Our results are in accordance with those of most of the aforementioned studies, as we found telomerase activity to be present in all normal colon tissue samples and in colon cancer tissue samples. Unfortunately, we did not have adenoma samples that could further enlighten the differences in telomerase activity and MLH1 expression in the various stages of CRC carcinogenesis.…”
Section: Discussionsupporting
confidence: 93%
“…33,34 Especially in those with ulcerative colitis, hTERT overexpression has been associated with induction of CIN, 34 possibly an effect of oxidative damage secondary to inflammation. 35 Our results are in accordance with those of most of the aforementioned studies, as we found telomerase activity to be present in all normal colon tissue samples and in colon cancer tissue samples. Unfortunately, we did not have adenoma samples that could further enlighten the differences in telomerase activity and MLH1 expression in the various stages of CRC carcinogenesis.…”
Section: Discussionsupporting
confidence: 93%
“…It has been proposed that telomere shortening with age may increase the risk of cancer (Blasco, 2005;Risques et al, 2008); this concept may be supported by our results, as telomere shortening between normal and neoplastic tissues was found to be inversely correlated with age. Although telomere length in somatic cells primarily reflects cellular proliferation, telomere length in tumour cells reflects the balance between cellular proliferation with telomere loss and telomerase activity with de novo synthesis of telomeric sequences.…”
Section: Discussionsupporting
confidence: 89%
“…15 We postulate that replicative exhaustion and subsequent cellular senescence of the intestinal stem cell compartment can at least partially explain clinical refractoriness of aGVHD despite sufficient immunosuppressive treatment. Further studies focusing on the analysis of nonrefractory aGVHD (milder disease) patient material, which is difficult to obtain because of obvious reasons, are warranted to reveal whether the degree of TL can be reversed in this patient population.…”
Section: Resultsmentioning
confidence: 98%